2014
DOI: 10.1016/j.vaccine.2013.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Oral polio vaccine response in breast fed infants with malnutrition and diarrhea

Abstract: Oral vaccines for polio (OPV) and rotavirus are less effective in children in the developing world. The reasons for this are not well understood. We tested for risk factors for poor response to OPV in infants from an urban slum of Dhaka, Bangladesh. Diminished serum neutralizing response to OPV, but not failure of intramuscularly administered vaccines, was associated with malnutrition, diarrhea, and shorter breastfeeding duration. Children with malnutrition (WAZ <−2) had significantly lower OPV 3 titers (p = 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 22 publications
3
54
0
1
Order By: Relevance
“…In spite of these immunological deficits, a consistent link between malnutrition and oral vaccine performance has not been found [108,109]. A recent study among infants in Bangladesh documented significantly lower serotype 3 poliovirus antibody titers in conjunction with underweight (weight-for-age Z score ≤2) after at least three doses of OPV [65]. However, other studies in India, Nigeria and Pakistan have not observed an association between malnutrition and OPV immunogenicity [110][111][112].…”
Section: Malnutrition and Micronutrient Deficienciesmentioning
confidence: 99%
See 3 more Smart Citations
“…In spite of these immunological deficits, a consistent link between malnutrition and oral vaccine performance has not been found [108,109]. A recent study among infants in Bangladesh documented significantly lower serotype 3 poliovirus antibody titers in conjunction with underweight (weight-for-age Z score ≤2) after at least three doses of OPV [65]. However, other studies in India, Nigeria and Pakistan have not observed an association between malnutrition and OPV immunogenicity [110][111][112].…”
Section: Malnutrition and Micronutrient Deficienciesmentioning
confidence: 99%
“…Later in infancy, the picture is more ambiguous -while an increase in the duration of breastfeeding was associated with a lower seroconversion rate (significant for serotype 3) following four doses of trivalent OPV among infants in Brazil, breastfeeding status had no effect on seroconversion rates during studies in Uganda [62] and India [63]. To confuse matters further, several studies have documented an improvement in OPV immunogenicity among breastfed infants [43,64,65].…”
Section: Breastfeedingmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is the intricate interplay between these variables that results in a particular metabolic state, and a key question is how immunity to vaccination is affected by such metabolic states. There are several studies documenting impaired immune responses associated with obesity (69,70) and undernutrition (71)(72)(73). Systems vaccinology offers a promising way to dissect the molecular mechanisms that result in impaired vaccine immunity in such abnormal conditions.…”
Section: Vaccines For Which There Are No Knownmentioning
confidence: 99%